Method of wall plastering / Fatin Nursyuhada Azmi - Azmi, Fatin Nursyuhada (Universiti Teknologi MARA UiTM,Perak, 2022)
Plastering is one of the common parts of the house, therefore it has many functions such as to protect the wall from the insect. This report will track down the method of wall plastering that were conducted in Taman Bunga Raya, Setapak, Kuala Lumpur for the one-story house that will be upgraded to two story house. The objective of the report is to identify the factors that should be considered in wall plastering, to identify the method of wall plastering, and to determine the problem and solution of wall plastering. It will focus on the type, advantages and disadvantages of the plaster that is used for the case study, the material and the tools that are used for the plastering. This report also reveals the first progress from concrete mixture until completion with all the details and pictures. This report discovers all the problems and solution of wall plastering.